2015
DOI: 10.1016/j.bbmt.2015.03.015
|View full text |Cite
|
Sign up to set email alerts
|

GLCCI1 and Glucocorticoid Receptor Genetic Diversity and Response to Glucocorticoid-Based Treatment of Graft-versus-Host Disease

Abstract: The genetic diversity of loci implicated in glucocorticoid (GC) response has been associated with interindividual variations in responsiveness to GC in various diseases, such as asthma and inflammatory bowel disorders. In acute graft-versus-host disease (aGVHD), similar differences of first-line therapy responsiveness are also observed, with approximately 40% of patients failing to respond to GC. Here, the distribution of functionally relevant single nucleotide polymorphisms (SNP) belonging to the GC-induced t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…The presence of the GCA haplotype in the recipient was also associated with increased risk of relapse ( p = 0.028, HR: 1.703, 95% CI: 1.047–2.768). Interestingly, a recent study investigating the influence of SNPS in the GCR in steroid sensitive and steroid resistant aGvHD found the presence of the G allele of rs6198 in the recipient showed a trend for association with steroid sensitive aGvHD, O'Meara et al () indicating that in a HSCT setting the G allele is the steroid sensitive allele. The presence of the ACT haplotype in the recipient was associated with cGvHD ( p = 0.046, OR: 2.012, 95% CI: 1.044–3.880), in the first cohort a trend for this association was also observed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The presence of the GCA haplotype in the recipient was also associated with increased risk of relapse ( p = 0.028, HR: 1.703, 95% CI: 1.047–2.768). Interestingly, a recent study investigating the influence of SNPS in the GCR in steroid sensitive and steroid resistant aGvHD found the presence of the G allele of rs6198 in the recipient showed a trend for association with steroid sensitive aGvHD, O'Meara et al () indicating that in a HSCT setting the G allele is the steroid sensitive allele. The presence of the ACT haplotype in the recipient was associated with cGvHD ( p = 0.046, OR: 2.012, 95% CI: 1.044–3.880), in the first cohort a trend for this association was also observed.…”
Section: Discussionmentioning
confidence: 99%
“…The G allele of rs6198 has been associated with rheumatoid arthritis (RA), Derijk et al (2001), Chatzikyriakidou et al (2009), heart disease, Van den Akker et al (2008) and reduced nasal carriage of staphylococcus aureus, Van den Akker et al (2006). More recently, a trend to an association has been found with the G allele of rs6198 in the patient and corticosteroid sensitive aGvHD, O'Meara et al (2015).…”
Section: Introductionmentioning
confidence: 99%
“…7 A study of Japanese patients showed that GLCCI1 rs37973 contributed to an annual decline in FEV1 of 30 mL/y or greater, in those receiving long-term ICS treatment. 19 The role of the GLCCI1 gene minor allele has been examined in patients with other chronic inflammatory diseases, rheumatoid arthritis, 20 graft-versus-host disease (GVHD) 21 and nephrotic syndrome. 22 In terms of sensitivity to GC, genetic variants might be associated with the response to GC therapy in male patients with RA, whereas rs37972 FIGU RE 2 Concentration-change and time course of GLCCI1 induction by fluticasone.…”
Section: Discussionmentioning
confidence: 99%
“…The protein structure predicts a 58 kDa protein with a coiled coil region and multiple putative S/T phosphorylation sites. Genetic polymorphism in the GLCCI1 gene, including its promoter region, has been associated with glucocorticoid response in asthma patients, pediatric nephrotic syndrome, and Graft-versus-Host disease ( Cheong et al, 2012 ; Chiba et al, 2018 ; O'Meara et al, 2015 ). Mechanistically, GLCCI1 promotes the binding between glucocorticoid receptor (GR) and GR-interacting protein 1 (GRIP1) but inhibits the recruitment of GRIP1 to interferon regulatory factors IRF1 and IRF3 ( Hu et al, 2021 ).…”
Section: Understanding the Function And Regulation Of Dyrk1a Through ...mentioning
confidence: 99%